2021
DOI: 10.1108/ihr-07-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y's dining out behavior

Abstract: PurposeThe purpose of this research is to examine the dining out activities of Gen Y's in the United States. In particular, it focuses on dining frequency, restaurant selection, restaurant segments and demographic features of Gen Yers.Design/methodology/approachEmpirical data for this study were collected from 631 Gen Y's living in the United States.FindingsThe research findings reveal a nascent exploration of eating out preferences of the Gen Y population in an industrialized country in the food service conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…, 2019; Yoon and Chung, 2017). However, this study’s results are consistent with the Okumus et al. (2021) study, which concluded that restaurant attributes like ambience, having a new experience, noise and crowd level are inconsequential for the millennial diner when choosing a restaurant.…”
Section: Discussion Of Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…, 2019; Yoon and Chung, 2017). However, this study’s results are consistent with the Okumus et al. (2021) study, which concluded that restaurant attributes like ambience, having a new experience, noise and crowd level are inconsequential for the millennial diner when choosing a restaurant.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…, 2017; Qin and Prybutok, 2008). Those new to food trucks use observable signals related to food truck image in the lines of S–O–R framework to form their perceptions along with factors such as cleanliness, food variety, service quality, food cost and service speed when selecting a restaurant (Okumus et al. , 2021).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Food quality affects tourist loyalty (Han & Hyun, 2017;Hernandez-Rojas et al, 2021;Zhong & Moon, 2020). The majority of respondents are from generations Y and Z where they are the most powerful generation and the most developed customer segment in the food industry compared to other generations (Nyheim et al, 2015;Okumus et al, 2021;Yoon & Chung, 2018;Yoon et al, 2018). Tourists are more concerned with quality food than luxurious service and still consider a comfortable place for their satisfaction (Okumus et al, 2021;Roseman et al, 2017;Zhong & Moon, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This study explains that East Java tourists are a customer segment that pays attention on the level of service quality in buying food. They tend to like fast service over getting the luxury services offered (Okumus et al, 2021;Wahyuningsih et al, 2022) The next hypothesis is the direct and mediating effect of the perceived authenticity variable. H3 is accepted and this study supports previous research that there is an important relation between loyalty and authenticity in cognitive and emotional-based constructs (Fu, 2019;Zhang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation